2016
DOI: 10.1155/2016/3915703
|View full text |Cite
|
Sign up to set email alerts
|

Reducedγ-Aminobutyric Acid and Glutamate+Glutamine Levels in Drug-Naïve Patients with First-Episode Schizophrenia but Not in Those at Ultrahigh Risk

Abstract: Altered γ-aminobutyric acid (GABA), glutamate (Glu) levels, and an imbalance between GABAergic and glutamatergic neurotransmissions have been involved in the pathophysiology of schizophrenia. However, it remains unclear how these abnormalities impact the onset and course of psychosis. In the present study, 21 drug-naïve subjects at ultrahigh risk for psychosis (UHR), 16 drug-naïve patients with first-episode schizophrenia (FES), and 23 healthy controls (HC) were enrolled. In vivo GABA and glutamate+glutamine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 67 publications
4
29
1
1
Order By: Relevance
“…Examining glutamatergic measures in the MPFC across illness stages, Natsubori and colleagues reported no alterations in Glx in the MPFC in subjects at ultrahigh risk for schizophrenia or FEP patients with no more than 16 weeks of cumulative antipsychotic medication exposure, but did report a decrease in Glx in chronic schizophrenia patients 42 . In contrast, Wang and colleagues did not find alterations in Glx in ultrahigh risk subjects, but reported reduced MPFC Glx in a small group of medication-naive FEP 43 . It stands to reason that illness stage could, at least in part, account for discrepancies in findings.…”
Section: Discussionmentioning
confidence: 81%
“…Examining glutamatergic measures in the MPFC across illness stages, Natsubori and colleagues reported no alterations in Glx in the MPFC in subjects at ultrahigh risk for schizophrenia or FEP patients with no more than 16 weeks of cumulative antipsychotic medication exposure, but did report a decrease in Glx in chronic schizophrenia patients 42 . In contrast, Wang and colleagues did not find alterations in Glx in ultrahigh risk subjects, but reported reduced MPFC Glx in a small group of medication-naive FEP 43 . It stands to reason that illness stage could, at least in part, account for discrepancies in findings.…”
Section: Discussionmentioning
confidence: 81%
“…familial) high-risk groups, such as reduced N-acetylaspartate in the thalamus Tandon et al, 2013;Yoo et al, 2009), ACC (Capizzano et al, 2011;Jessen et al, 2006), and caudate (Keshavan et al, 2009)-although increases are also observed in the caudate (de la Fuente-Sandoval et al, 2011). Increased Glx has been reported in the thalamus and caudate, as well as increased (de la or decreased (Menschikov et al, 2016) medial prefrontal GABA-although differences are not always found (Modinos et al, 2018b;Wang et al, 2016). Finally, other studies have reported increased choline in the ACC (Tandon et al, 2013), prefrontal cortex (Wood et al, 2003) and hippocampus (Capizzano et al, 2011) in populations at risk for psychosis.…”
Section: <Figure 1>mentioning
confidence: 99%
“…Here glutamate is found unaltered in antipsychotic naive [11,18] and minimally treated [17,19,20] patients with schizophrenia, but reports of increased glutamine levels in antipsychotic naive patients [11,18] are supported by findings of increased glx levels in the overlapping medial prefrontal cortical region of unmedicated patients ( [21,22]). Unaltered glutamine levels in first episode [23] and lower glx levels in antipsychotic naive patients [24] are also reported in prefrontal cortex. Studies in chronic patients have generally found decreased [13,25,26] or unaltered [27,28] levels of glutamate and glutamine in the ACC.…”
Section: Introductionmentioning
confidence: 99%